G330(P) Brain biopsy in children being investigated for undiagnosed neurological conditions. (7th April 2014) - Singh, A; Iyer, A; Burn, S; Malluci, C; Appleton, RE; Splinty, S; Baborie, A; Kneen, R
Abstract : Objective: Brain biopsy has a diagnostic yield of >95% in neoplastic conditions. There is limited knowledge about the usefulness of brain biopsy in children with undiagnosed neurological conditions and the aim of this audit is to address this issue; therefore we undertook an audit of these patients. Methods: This was a retrospective, five-year case-note review of brain biopsies requested by neurologists in a tertiary children's hospital (2008–2013). Information was collected on clinical features, neuroimaging, investigationsand histology reports. Results: Twelve (eight male) patients were identified. Median (range) age was 9.5 (2–16) years. The considered clinico-radiological diagnosis pre-biopsy included: non-neoplastic space occupying lesion (n = 5), central nervous system (CNS) vasculitis (n = 3), encephalitis (n = 2), neurosarcoidosis (n = 1) and pachymenigitis (n = 1). Presenting features included: signs of raised intracranial pressure (n = 4); cerebellar signs [(n = 3, one with growth failure and diabetes insipidus and another with a progressive paraparesis]; encephalitis with seizures and a movement disorder (n = 1); steroid dependent encephalitis (n = 1); transient ischaemic attacks (n = 2) and neurological regression with a movement disorder and epilepsy (n = 1). Twelve biopsies were from the identified lesion and two were from non-lesional from the frontal lobe (suspected CNS vasculitis). Two children (suspected neurosarcoidosis and pachymeningitis) had repeat lesional biopsies before immunosuppressant treatment was started. A definite diagnosis was identified in eight: demyelination (n = 3); grade II astrocytomas (n = 2); HSV co-infection in a case of known NMDAR encephalitis; granulomatous meningitis (consistent with neurosarcoidosis) and Rosenthal fibres (consistent with atypical Alexander's with negative glial fibrillary acidic protein (GFAP) stain. Biopsy in one showed non-specific features of encephalitis and three biopsies were unremarkable. Histological results gave useful information in call cases and altered the management in 10 cases. Complications included: subdural effusion [n = 1 (spontaneous resolution)], suspected meningitis (no LP undertaken) n = 1, late superficial wound infection n = 1. All recovered fully. Conclusion: Brain biopsy appears to have a useful role in some children with undiagnosed neurological disorders. The procedure should be considered if the findings are likely to alter management or to establish a specific diagnosis of a degenerative condition, or both. One quarter had an acute complication with no long term sequalae. The long term effects are unknown.